2015
DOI: 10.1039/c5sc00720h
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite reduction by copper through ligand-mediated proton and electron transfer

Abstract: A copper complex featuring a proton-responsive tripodal ligand reduces nitrite via a proton/electron transfer process, which parallels copper nitrite reductase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 45 publications
3
58
0
Order By: Relevance
“…[6][7][8] Aw idely accepted mechanism of copper-mediated nitrite reduction implicates the intermediacyo fa{CuNO} 10 species (Enemark-Feltham notation [9] )w hich readily releases NOC (Scheme 1B). [13] Despite the significant interest in the bioinorganic chemistry of copper nitrosyl complexes in the past decades, [14] the study of NOC coordination to copper centers has been relatively underdeveloped. [13] Despite the significant interest in the bioinorganic chemistry of copper nitrosyl complexes in the past decades, [14] the study of NOC coordination to copper centers has been relatively underdeveloped.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Aw idely accepted mechanism of copper-mediated nitrite reduction implicates the intermediacyo fa{CuNO} 10 species (Enemark-Feltham notation [9] )w hich readily releases NOC (Scheme 1B). [13] Despite the significant interest in the bioinorganic chemistry of copper nitrosyl complexes in the past decades, [14] the study of NOC coordination to copper centers has been relatively underdeveloped. [13] Despite the significant interest in the bioinorganic chemistry of copper nitrosyl complexes in the past decades, [14] the study of NOC coordination to copper centers has been relatively underdeveloped.…”
mentioning
confidence: 99%
“…[10][11][12] However,due to the lack of synthetic and biological examples of {CuNO} 10 species,t he validity of a{ CuNO} 10 intermediate in the mechanism of CuNiR has been brought into question. [13] Despite the significant interest in the bioinorganic chemistry of copper nitrosyl complexes in the past decades, [14] the study of NOC coordination to copper centers has been relatively underdeveloped. Kohlschütter originally reported the binding of NOC to copper(II) halides (Cu II X 2 ,X= Cl, Br) to form putative {CuNO} 10 complexes more than 100 years ago.…”
mentioning
confidence: 99%
“…Our lab [11] and others [12] have shown that ligands featuring the 2-hydroxypyridine (2-hp) fragment can be employed for cooperative substrate binding, proton-coupled electron transfer, and catalysis. [13] The combination of a metal halide H-bond acceptor [14] with a rigid planar ligand featuring pendent hydroxyl H-bond donors was hypothesized to bind Cu(I) in a square planar geometry.…”
mentioning
confidence: 99%
“…[13] The combination of a metal halide H-bond acceptor [14] with a rigid planar ligand featuring pendent hydroxyl H-bond donors was hypothesized to bind Cu(I) in a square planar geometry. Cu(I) complexes with the ligand, 6,6″-dihydroxyterpyridine (dhtp), [11a] which incorporates two 2-hp fragments, was initially explored. Unfortunately, rather than affording the desired square planar compounds, metalations using CuCl with dhtp resulted in the formation of multinuclear clusters (Figure 1, top).…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Soil bacteria metabolise nitrite to NO by means of nitrite reductases, which are enzymes of the EC 1.7 group [27] with iron-, [28] copper- [29] or molybdenum-based [26] active centres. [21] Despite such great importance,t he chemical homogeneous reduction of nitrites by inorganic transition metals and internal transition-metal compounds has rarely been investigated.M ost studies focusedo ni ron [33][34][35][36][37][38][39][40][41][42][43][44][45] or copper [46][47][48][49][50][51][52] complexes that mimicked nitrite reductases.H owever,N O 2 À reduction with Ru, [53] Mo, [54][55][56] Ti,C r, [56] Co [57][58][59] andU [60] was also reported. Various fungi, including A. muscaria,a lso contribute to the nitrogen cycle with nitrite as possible metabolic substrate.…”
Section: Introductionmentioning
confidence: 99%